2019
DOI: 10.1097/ijg.0000000000001181
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Interocular Asymmetry of Visual Field Defects and Optic Nerve Head Blood Flow in Patients With Glaucoma

Abstract: Purpose: To investigate the association between asymmetry of visual field (VF) defects and optic nerve head (ONH) blood flow in patients with glaucoma using laser speckle flowgraphy. Methods: In total, 170 eyes of 85 patients with primary open-angle glaucoma were included. Intraocular pressure, VF (Humphrey 24-2, SITA program), mean blur rate in the tissue area (MBR-T) of the ONH measured by laser speckle flowgraphy, axial length, circumpapillary retina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…This is in keeping with a previous smaller-scale study in glaucoma patients [ 21 ]. Whereas several previous studies have shown that there is an association between ONH and/or retinal blood flow with glaucoma damage [ 22 , 23 , 24 , 25 , 26 , 27 ], our study links RGC damage to oxygen metabolism.…”
Section: Discussioncontrasting
confidence: 53%
“…This is in keeping with a previous smaller-scale study in glaucoma patients [ 21 ]. Whereas several previous studies have shown that there is an association between ONH and/or retinal blood flow with glaucoma damage [ 22 , 23 , 24 , 25 , 26 , 27 ], our study links RGC damage to oxygen metabolism.…”
Section: Discussioncontrasting
confidence: 53%
“…Firstly, asymmetric NTG was defined as an MD difference of at least 3 dB in the present study. The definition of asymmetric VF loss was inconsistent in previous articles with an MD difference from 0.01 to 6 dB [40,41]. The greater the difference of MD, the more the reliable risk factors can be found.…”
Section: Discussionmentioning
confidence: 97%
“…Although the underlying mechanisms leading to glaucomatous atrophy in PACG cases are not fully understood, several mechanisms have been suggested. For example, inflammation [3], microangiopathy [4][5][6][7][8][9] and oxidative stress [10,11] are all currently being discussed in terms of the leading factors causing PACG, which can damage the optic nerve and lead to the progressive loss of retinal ganglion cells and their axons.…”
Section: Introductionmentioning
confidence: 99%